2020
DOI: 10.1136/bmj.m3734
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells for minimising immune suppression in kidney transplantation: phase I/IIa clinical trial

Abstract: ObjectiveTo assess whether reshaping of the immune balance by infusion of autologous natural regulatory T cells (nTregs) in patients after kidney transplantation is safe, feasible, and enables the tapering of lifelong high dose immunosuppression, with its limited efficacy, adverse effects, and high direct and indirect costs, along with addressing several key challenges of nTreg treatment, such as easy and robust manufacturing, danger of over immunosuppression, interaction with standard care drugs, and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
132
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 50 publications
3
132
0
Order By: Relevance
“…Intriguingly, ART treatment also dramatically enhanced the expansion of Treg cells, which play a central role in transplant tolerance. This is consistent with other assays and our previously published data showing that Treg cell therapy could significantly alleviate renal allograft injury and induce immune tolerance in animal and clinical trials (27,28). Our data thus showed that ART could effectively inhibit TCMR and induce Treg cell expansion.…”
Section: Discussionsupporting
confidence: 93%
“…Intriguingly, ART treatment also dramatically enhanced the expansion of Treg cells, which play a central role in transplant tolerance. This is consistent with other assays and our previously published data showing that Treg cell therapy could significantly alleviate renal allograft injury and induce immune tolerance in animal and clinical trials (27,28). Our data thus showed that ART could effectively inhibit TCMR and induce Treg cell expansion.…”
Section: Discussionsupporting
confidence: 93%
“…Published data from Treg cell therapy trials in transplantation provide some cause for cautious optimism, with evidence for safety and perhaps a reduced requirement for induction immunosuppression in renal transplantation [58] or even maintenance immunosuppression in liver transplantation [59]. A recent study in 11 kidney transplant patients demonstrated that stable monotherapy immunosuppression was achieved in 8 patients receiving autologous Treg [60]. While these trials are still in early phases, the benefits of reducing immunosuppression are becoming apparent in terms of lower viral infection rates and normalization of immune composition [58].…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…The study of Roemhild et al . [60] reported a transient increase in Treg levels with a return to control levels 12 weeks after administration of Tregs. For other cell types, survival times are not clear, and the use of autologous cells in clinical studies hampers long‐term tracking.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…One approach would be to adoptively transfer ex vivo expanded Tregs back into the patient. In fact clinical trials in kidney transplantation showing improved clinical outcomes in some patients suggest that transfer of autologous Tregs can be promising across multiple immune-dysfunctional conditions (53)(54)(55). In addition, modifying the Tregs ex vivo before transplanting them back into the patient may increase efficacy and avoid potential systemic immunosuppression.…”
Section: Resultsmentioning
confidence: 99%